2021
DOI: 10.1080/10556788.2020.1850720
|View full text |Cite
|
Sign up to set email alerts
|

Solving SDP completely with an interior point oracle

Abstract: We suppose the existence of an oracle which solves any semidefinite programming (SDP) problem satisfying strong feasibility (i.e. Slater's condition) simultaneously at its primal and dual sides. We note that such an oracle might not be able to directly solve general SDPs even after certain regularization schemes are applied. In this work we fill this gap and show how to use such an oracle to 'completely solve' an arbitrary SDP. Completely solving entails, for example, distinguishing between weak/strong feasibi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…In this case, as described below, we can find a scaling such that the sum of eigenvalues of any feasible solution of P S ∞ (A) is bounded by r . Let H be the set of indices i satisfying (11) for each block . According to Proposition 3.5, set…”
Section: Proposition 36 Suppose That For Anymentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, as described below, we can find a scaling such that the sum of eigenvalues of any feasible solution of P S ∞ (A) is bounded by r . Let H be the set of indices i satisfying (11) for each block . According to Proposition 3.5, set…”
Section: Proposition 36 Suppose That For Anymentioning
confidence: 99%
“…In general, it is difficult to solve such problems stably by using interior point methods, but since strong complementarity exists between (P) and (D), they can be expected to be stably solved. By applying Lemma 3.4 of [11], we can generate a problem in which both the primal and dual problems have feasible interior points in which it can be determined whether (P) has a feasible interior point. However, since there was no big difference between the solution obtained by solving the problem generated by applying Lemma 3.4 of [11] and the solution obtained by solving the above (P) and (D), we showed only the results of solving (P) and (D) above.…”
Section: Outline Of Numerical Implementationmentioning
confidence: 99%
“…While many of the earlier papers on facial reduction focused on weakly feasible problems, it is relatively recent that weak infeasibility is analyzed in this context [15,18,29]. Along this line of developments, the paper [20] showed that, through double facial reduction, any SDP can be solved "completely" by calling an interiorpoint oracle polynomially many times, where the interior-point oracle is an idealized interior-point algorithm which return primal-dual optimal solutions given a primaldual strongly feasible SDP. In the context of SDPs with positive duality gaps, Ramana developed an extended Lagrangian dual SDP for which strong duality always holds [34].…”
Section: Introductionmentioning
confidence: 99%